European Union direct investment in China : characteristics, challenges and perspectives - Bulcke, D. van den (Studies in global competition., 2003)
China's immersion in the world economy and trading system is a continued source of great interest throughout the globe. The book is divided into three parts, the first being an overview of the Chinese investment environment and the development of foreign direct investment (FDI) over the last twenty years. The second part then goes on to focus specifically on the characteristics of European companies involved in FDI into China. The third part looks at different management aspects of EU invested enterprises within China, using newly acquired data. This comprehensive overview of European di.